Why did the Norwegian experiment with “sustainable towns” fail? - Langeland, Anders (Proceedings from the Annual Transport Conference at Aalborg University, 2001)
This paper addresses the question: Why did the Norwegian experiment with “sustainable towns” fail? Both the Government and the five appointed “sustainable towns” (ST) made a strong effort to succeed and the best planning expertise were available as advisers? The Government evaluation reports, the town reports and an earlier study by the author “Kristiansand 1945-1995. An analysis of planning, implementation and results.” are the main data sources for this article.